"The Natural World": An Eco-Justice Case Study, 1972–1992 - Quick, Beth (Methodist history, 2024)
This article explores the history of the United Methodist Social Principles as a case study, from their commissioning in 1968 and adoption in 1972 through several quadrennia of implementation, debate, and revision by General Conference sessions, in order to examine the eco-justice movement and the place of nonhuman animals in United Methodist polity. Focusing on the section of the Principles titled “The Natural World,” the author traces language related to concepts of the eco-justice movement, creation care, and nonhuman animals. Examining both proposed and adopted language at General Conferences, the author attends to which individuals and organizations, including caucus groups, advocated for changes related to “The Natural World” Social Principles. Exploring how eco-justice concerns become part of the social justice framework of The UMC over time, the article also examines how changes occur within the denomination, and who has influence within official structures.